The Civilisational and Cultural Heritage of Iran and The Malay World: A Cultural Discourse - Zaid Ahmad, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
There has been a long-standing debate among historians and researchers about the forms and patterns of cultural interconnections, interactions and influences that took place along with the spread of Islam to various part of the world. Similarly, the interconnection between the Persian civilization and the Malay world is no exception. By Persian civilization I mean the civilization that was established long before the existence of the present Islamic Republic of Iran. Historically, the interaction between the Middle East (including Persian) and Southeast Asia (including Malay Archipelago) had already taken place as early as during the first and second century Islam.